Emerging use of combination therapies for the management of type 2 diabetes – focus on saxagliptin and dapagliflozin - Yu H (Dove Medical Press, 2017)
Huan Yu, Vincent C Woo Department of Medicine, Division of Endocrinology and Metabolism, Health Sciences Centre, University of Manitoba, Winnipeg, MB, Canada Aims: The aim of this article is to review the safety and efficacy data of dapagliflozin, saxagliptin, and their combination in the management of patients with type 2 diabetes. Evidence for the use of the single-tablet combination formulation is also presented. Methods: A nonsystematic literature review was performed using the Ovid, PubMed, and Google Scholar databases. Results: The addition of dapagliflozin/saxagliptin to metformin can lower mean hemoglobin A1c by as much as 1.47% and lead to weight loss of 0.5–2.0 kg. The risk of genital infections with combination therapy is lower than observed with dapagliflozin alone, suggestive of a protective effect. Adverse event risk at 52-week follow-up was not increased beyond that seen with either monotherapy. Conclusion: Dapagliflozin/saxagliptin combination is generally well tolerated and is an effective tool in helping patients with diabetes improve glycemic control. Keywords: SGLT2 inhibitor, DPP4 inhibitor, single-tablet combination, diabetes mellitus